Unveiling Perspectives: Understanding Women’s Political Involvement in India - Challa, Pranavi; Kothari , Jitender (Trinity Law Review, 2025)
Susan B. Anthony, a prominent American social reformer and women's rights activist, famously stated, "Men, their rights, and nothing more; women, their rights, and nothing less1." This powerful quote encapsulates the core principle of gender equality and the fight for women's rights. Anthony played a pivotal role in the women's suffrage movement in the United States, which sought to secure the right to vote for women. The American suffrage ca mpaign was gr eatly influenced by the Ind ian suff ragette movement, which demonstrated the long history of women's engagement and participation in political activities in India. Prominent individuals such as Naidu championed for enhanced availability of education for females and women in India, stressing the metamorphic potential of education for women. Women make up around half of the world's population, so it is critical to acknowledge the significance of their viewpoints, experiences, and expectations. Only when all facets of society— including women—are actively involved and represented will true democracy be realised. Legislation that advances gender equality and tackles urgent problems like pay disparities, women's rights, and access to healthcare and education can be supported by women in leadership positions. Furthermore, female politicians serve as inspirational role models for upcoming generations. Their presence encourages young girls and women to pursue careers in politics and other leadership roles. The legitimacy and trustworthiness of government institutions are enhanced when the political leadership include a diverse range of individuals from the populations they serve. The study report consists of a survey that twenty participants answered to gauge their comprehension of current data, historical trends, and the importance of gender diversity in governance. It explores people's views on gender equality, the barriers that prevent women from participating in politics, and the impact of women in leadership positions. These investigations seek to investigate several things, such as institutional biases, cultural attitudes, and society norms.
Keywords: gender parity; sta tistics of female representation; government policies; legal ref ormation; survey